2021
DOI: 10.3389/fgene.2021.686000
|View full text |Cite
|
Sign up to set email alerts
|

Epitranscriptomic Analysis of m6A Methylome After Peripheral Nerve Injury

Abstract: N6-methyladenosine (m6A) is one of the most plentiful internal RNA modifications, especially in eukaryotic messenger RNA (mRNA), which plays pivotal roles in the regulation of mRNA life cycle and nerve development. However, the mRNA m6A methylation pattern in peripheral nervous injury (PNI) has not been investigated. In this study, sciatic nerve samples were collected from 7 days after sciatic nerve injury (SNI) and control rats. Quantitative real-time PCR demonstrated that m6A-related methyltransferase/demeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…Our previous study demonstrated that the epigenetic network is essential for vascular regeneration and functional recovery post-SCI ( Ni et al, 2019 ). The m 6 A methylation plays a significant role in the pathological process of corneal injury, brain injury, and peripheral nerve injury ( Weng et al, 2018 ; Wang et al, 2019 ; Dai et al, 2021 ; Zhang et al, 2021 ). In contrast, various types of cancers and diabetes are associated with lowered m 6 A abundance ( Chen et al, 2020 ; Huang et al, 2021 ; Lei et al, 2021 ; Ruan et al, 2021 ; Wang et al, 2021a ; Ye et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that the epigenetic network is essential for vascular regeneration and functional recovery post-SCI ( Ni et al, 2019 ). The m 6 A methylation plays a significant role in the pathological process of corneal injury, brain injury, and peripheral nerve injury ( Weng et al, 2018 ; Wang et al, 2019 ; Dai et al, 2021 ; Zhang et al, 2021 ). In contrast, various types of cancers and diabetes are associated with lowered m 6 A abundance ( Chen et al, 2020 ; Huang et al, 2021 ; Lei et al, 2021 ; Ruan et al, 2021 ; Wang et al, 2021a ; Ye et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, m 6 A modification is supposed to be highly relevant to gut microbiota (Jabs et al, 2020), heat shock proteins (Feng et al, 2020), sepsis (Sun et al, 2020;Xing et al, 2021), and pulmonary hypertension (Pan et al, 2020) and even peripheral nerve injury (Zhang L et al, 2021). These studies can provide valuable experimental basis for development of new treatments.…”
Section: Discussionmentioning
confidence: 99%
“…After nerve injury, m6A modification may have the function of regulating axonal regeneration and synaptic regeneration. Zhang et al (2021b) performed MeRIP-seq to reveal the m6A methylation landscape in peripheral nervous injury (PNI). They found that 4,014 m6A peaks were significantly altered after PNI.…”
Section: Possible Research Directions Of N6-methyladenosine Modificat...mentioning
confidence: 99%
“…They found that 4,014 m6A peaks were significantly altered after PNI. Moreover, GO analysis and KEGG pathway analysis showed that these genes were mainly involved in axon regeneration ( Zhang et al, 2021b ). Furthermore, Wang X. L. et al (2022) reported that in a mouse neuropathic pain (NP) model, downregulation of FTO in the anterior cingulate cortex (ACC) could promote angiogenesis, axon growth and neural plasticity as proven by up-regulation of matrix metalloproteinase-9 (MMP-9), decreased levels of precursor brain-derived neurotrophic factor (proBDNF) and increased levels of mature brain-derived neurotrophic factor (mBDNF).…”
Section: Possible Research Directions Of N6-methyladenosine Modificat...mentioning
confidence: 99%